2003
DOI: 10.1021/jm030166l
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Design, Synthesis, and Biological Evaluation of Irreversible Human Rhinovirus 3C Protease Inhibitors. 8. Pharmacological Optimization of Orally Bioavailable 2-Pyridone-Containing Peptidomimetics

Abstract: The optimization of the pharmacokinetic performance of various 2-pyridone-containing human rhinovirus (HRV) 3C protease (3CP) inhibitors following oral administration to either beagle dogs or CM-monkeys is described. The molecules described in this work are composed of a 2-pyridone-containing peptidomimetic binding determinant and an alpha,beta-unsaturated ester Michael acceptor moiety which forms an irreversible covalent adduct with the active site cysteine residue of the 3C enzyme. Modification of the ester … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
63
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(64 citation statements)
references
References 35 publications
1
63
0
Order By: Relevance
“…Replacement of the P 2 benzylic substituent in compound XVIII with a propynyl fragment furnished the irreversible inhibitor ''compound XXI,'' also referred to as ''compound 1'' (Table II). 334,352 This compound demonstrated oral bioavailability in dogs and CM-monkeys with 7-hr plasma concentrations similar to or exceeding the in vitro antiviral activity against the seven HRV serotypes evaluated. 352 In addition, in cell-based assays, the compound was active against 35 different HRV genotypes, against 5 clinical isolates and 8 related picornaviruses with EC 50 values ranging between 7 and 249 nM (Table II).…”
Section: Tripeptidyl A-ketoamidesmentioning
confidence: 88%
See 3 more Smart Citations
“…Replacement of the P 2 benzylic substituent in compound XVIII with a propynyl fragment furnished the irreversible inhibitor ''compound XXI,'' also referred to as ''compound 1'' (Table II). 334,352 This compound demonstrated oral bioavailability in dogs and CM-monkeys with 7-hr plasma concentrations similar to or exceeding the in vitro antiviral activity against the seven HRV serotypes evaluated. 352 In addition, in cell-based assays, the compound was active against 35 different HRV genotypes, against 5 clinical isolates and 8 related picornaviruses with EC 50 values ranging between 7 and 249 nM (Table II).…”
Section: Tripeptidyl A-ketoamidesmentioning
confidence: 88%
“…334,352 This compound demonstrated oral bioavailability in dogs and CM-monkeys with 7-hr plasma concentrations similar to or exceeding the in vitro antiviral activity against the seven HRV serotypes evaluated. 352 In addition, in cell-based assays, the compound was active against 35 different HRV genotypes, against 5 clinical isolates and 8 related picornaviruses with EC 50 values ranging between 7 and 249 nM (Table II). 334 In vitro and in vivo non-clinical safety studies showed compound XXI to be without adverse effects at maximum achievable doses.…”
Section: Tripeptidyl A-ketoamidesmentioning
confidence: 88%
See 2 more Smart Citations
“…The effectiveness V-073 in treating neonatal enteroviral sepsis was recently reported (70), and V-073 is currently in a clinical trial as an anti-PV antiviral (EudraCT Number: 2011-004804-38). Viral 2A protease, 2C helicase, 3C protease, and 3D polymerase have also been identified as potential targets of direct-acting antiviral agents, including elastase inhibitors (2A inhibitor) (71), guanidine hydrochloride and related compounds (2C inhibitor) (72)(73)(74)(75), rupintrivir (AG-7088) or AG-7404 (3C inhibitor) (76)(77)(78), and ribavirin (79,80), respectively. However, the efficacy of these candidates against PV infection in vivo remains to be clarified.…”
Section: Overview Of Ongoing Pv Studies In the Polio Endgamementioning
confidence: 99%